Deciphering the anti-obesity mechanisms of pharmabiotic probiotics through advanced multiomics analysis - Ye-Rim Kim; Tae-Rim Choi; Sung-Hyun Jo; Won-Suk Song; TaeHyun Kim; Min-Gyu Kim; Ji-Hyun Baek; Seo-Young Kwon; Bo-Gyeong Choi; Sang Woo Seo; Chol-Soon Jang; Yung-Hun Yang; et al. (iScience)
Summary: Probiotics with “pharmabiotic” properties are increasingly recognized as effective tools for combating obesity by altering gut microbiota and reducing body fat. However, the molecular mechanisms underlying their anti-obesity effects remain largely unexplored due to the absence of a universal methodology. Herein, we developed a multiomics-based strategy to elucidate how probiotics reduce lipid production in adipocytes. Our initial investigation assessed the impact of probiotics at defined adipocyte differentiation stages. Leveraging these insights, we performed comprehensive multiomics analyses at key intervals to identify the suppression mechanisms of lipid formation. Lactobacillus reuteri, specifically, targets early differentiation stages, inhibits branched-chain amino acid catabolism, and reduces lipid accumulation in adipocytes by suppressing Krüppel-like factor 5. Concurrently, enhanced hypoxia-inducible factor 1 expression impedes adipogenesis by downregulating lipin-1 expression. This study not only demonstrates the effectiveness of our approach in revealing complex host-microbe interactions but also significantly advances probiotic therapeutic development, offering promising avenues for obesity management.